Formal Specification, Testing and Verification on the Truck Simulation - Muhammad Iman Santoso; Bernd Noche; Asep Ridwan; Achmad Bahauddin; Ratna Ekawati; Muhammad Indrahanif (Operational Excellence in Logistics and Supply Chains: Optimization Methods, Data-driven Approaches and Security Insights. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 22, 2015)
Truck operation for the fertilizer handling in the one of Indonesia's Port turned out to be inefficient and produced long queues (1.3 hours) when operated in the maximum number of trucks, i.e. 30 units - 30 tons load capacity per unit. This paper presents a simulation-based optimization for scheduling quantity and capacity of the fertilizer trucks to achieve handling-target within 24 hours and reduce queue. New procedural technique that combine statistical, modeling, simulation and verification have been developed employing several tools and managed in a structural way using formal specification. Those techniques optimize the truck operation turn into 8 units and also decrease the round trip operation from 220 rounds into 217 rounds. It generates a daily productivity of 6516 tons and minimize truck queue until 0.14 hour. The reduction of resources utilization and queue time will diminish the total fertilizer handling cost.
10419/209191; https://econpapers.repec.org/RePEc:zbw:hiclpr:22
Keywords: 650; Fertilizer Truck; Formal Specification; Simulation; Verification